SPECIFIC REQUIREMENTS OF YOUTH WITH PHYSICAL DISABILITIES IN ONLINE BUSINESS - Amin, Aizan Sofia (International Journal of Psychosocial Rehabilitation, 2020)
Disabled people often argued to have a lower socio-economic level than non-disabled as a result of low access to health, transport, education, employment and information, especially in developing countries such as Malaysia. To overcome these employment challenges, disabled people especially youth with physical disabilities, should be encouraged to adopt the self-employment approach such as online business to generate income. Therefore, this article aims to identify the specific requirements in online business for youth with physical disabilities. This research employed a quantitative (survey) method. An online survey was conducted on 101 youths with physical disabilities in Malaysia to identify their specific requirements in online business. This research used descriptive analysis using values such as mode, median, mean and percentage to indicate the results of a given data. There are two types of needs for youth with physical disabilities in online entrepreneurship which were skills and support requirements. The results showed that there were six skills needed such as photography techniques, business management, financial management, business planning, marketing techniques and customer service management. Also, there are four support needs, namely, financial support, business knowledge support, skills support and social support. The findings have implications for those working with disabled people to design specific programs that fulfil the specific requirements of youth with physical disabilities in online business.